'That thing of human rights': discourse, emergency assistance, and sexual violence in South Sudan's current civil war. (27th December 2017) - Luedke, Alicia Elaine; Logan, Hannah Faye
Abstract : One of the most widely covered aspects of the current conflict in South Sudan has been the use sexual violence by rival factions of the Sudan People's Liberation Movement/Army (SPLM/A) and other armed groups. While this has had the positive effect of ensuring that sexual violence is an integral component of intervention strategies in the country, it has also had a number of unintended consequences. This paper demonstrates how the narrow focus on sexual violence as a 'weapon of war', and the broader emergency lens through which the plight of civilians, especially women, has been viewed, are overly simplistic, often neglecting the root causes of such violence. More specifically, it highlights how dominant discourses on sexual violence in South Sudan's conflict have disregarded the historically violent civil–military relations that have typified the SPLM/A's leadership, and the structural violence connected with the local political economy of bride wealth and the associated commodification of feminine identities and bodies.